Ultimate Guide to Outpatient Care - Sarwar Zaman, Gaffar (IntechOpen, 2022)
The book presents a qualitative and quantitative approach to understanding, managing, and collaborating outpatient care. Utilizing a sound theoretical and practical foundation and illustrating procedural techniques through scientific examples, this book provides a comprehensive overview of outpatient care whether it occurs via telemedicine or in a hospital, clinic, prison, school, or other settings.